The complete mitochondrial genome of the hemiparasitic mistletoe Psittacanthus palmeri (Loranthaceae) and comparative analysis of mitogenomes across Santalales - Saddan Morales-Saldaña; Juan Francisco Ornelas (Botan‪ical Sciences)
Background: In parasitic plants, it remains uncertain whether size, structure, and mutation rates in the mitogenome aligns with those of other angiosperms, and whether reduction in gene content is found across lineages of parasitic plants.